The promise of fintech : financial inclusion in the post COVID-19 era - Sahay, Ratna (Washington, D.C Fonds Monetaire International, 2020)
​Technology is changing the landscape of the financial sector, increasing access to financial services in profound ways. These changes have been in motion for several years, affecting nearly all countries in the world. During the COVID-19 pandemic, technology has created new opportunities for digital financial services to accelerate and enhance financial inclusion, amid social distancing and containment measures. At the same time, the risks emerging prior to COVID-19, as digital financial services developed, are becoming even more relevant. (IMF Page)
​Acknowledgments -- Glossary and Definitions -- Executive Summary -- 1. Introduction -- 2. Setting the Stage: Recent Global Developments and Literature Review -- 3. Where Is Fintech for Financial Inclusion Emerging? -- 4. Is Fintech Increasing Financial Inclusion? - 5. What Are the Macroeconomic Implications? -- 6. Are Fintech Companies Disrupting Traditional Providers? -- 7. What Are the Factors that Enable and Constrain Digital Financial Inclusion? -- 8. What Are the Risks of Fintech to Financial Inclusion? -- Acknowledgments -- Glossary and Definitions -- Executive Summary -- 1. Introduction -- 2. Setting the Stage: Recent Global Developments and Literature Review -- 3. Where Is Fintech for Financial Inclusion Emerging? -- 4. Is Fintech Increasing Financial Inclusion? - 5. What Are the Macroeconomic Implications? -- 6. Are Fintech Companies Disrupting Traditional Providers? -- 7. What Are the Factors that Enable and Constrain Digital Financial Inclusion? -- 8. What Are the Risks of Fintech to Financial Inclusion?
Includes bibliographical references (p: 61-67)
Keywords: Banks and Banking; Financial services industry; Social aspects; TECHNOLOGICAL INNOVATIONS; COVID-19